2016
DOI: 10.1016/j.scriptamat.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

From glissile to sessile: Effect of temperature on 〈110〉 dislocations in perovskite materials

Abstract: In perovskite-type strontium titanate (SrTiO 3 ) 〈110〉 dislocations, which are the main carriers of plastic flow at low temperature, lose their mobility as temperature increases, leading to brittle failure above 1050 K. We present theoretical evidence for a change in their core structure into a sessile, climb-dissociated configuration at high temperature. This mechanism is shown to operate in both SrTiO 3 and MgSiO 3 , indicating that it may be a general feature of perovskite-type materials. It follows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…The simulations indicate that within the glide plane the dislocations tend to dissociate in two partial dislocations with distances of 4-5 nm separated by a strongly distorted antiphase boundary stacking fault [216]. The gliding of dislocations is also strongly temperature-dependent since it was calculated that at high temperatures the dislocations lose their mobility leading to brittle behavior of the crystal [105]. By employing a concurrent atomistic continuum simulation Yang et al [95] also confirmed the importance of easy glide planes in SrTiO 3 resulting in a preference of the <110> directions for dislocation nucleation and revealed that the presence of an agglomeration of dislocations in form of bicrystalline boundaries in SrTiO 3 has a significant effect on the mechanical properties and the crack evolution [97].…”
Section: Molecular Atomic Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulations indicate that within the glide plane the dislocations tend to dissociate in two partial dislocations with distances of 4-5 nm separated by a strongly distorted antiphase boundary stacking fault [216]. The gliding of dislocations is also strongly temperature-dependent since it was calculated that at high temperatures the dislocations lose their mobility leading to brittle behavior of the crystal [105]. By employing a concurrent atomistic continuum simulation Yang et al [95] also confirmed the importance of easy glide planes in SrTiO 3 resulting in a preference of the <110> directions for dislocation nucleation and revealed that the presence of an agglomeration of dislocations in form of bicrystalline boundaries in SrTiO 3 has a significant effect on the mechanical properties and the crack evolution [97].…”
Section: Molecular Atomic Simulationmentioning
confidence: 99%
“…Because the diffusion of oxygen vacancies is easier than that of cation vacancies, this process cannot be realized in only one step. The detailed scenario of all steps of the climbing of the dislocations in this electrical complicated surrounding has been described by Hirel et al [105]. e.g., [10,42,[99][100][101][102][103][104]).…”
Section: Arrangement Of Dislocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic interaction is modeled using the rigid-ion potential of Thomas et al, 38 which consists of a long-range Coulomb and a short-range cation-oxygen interaction term of Born-Mayer type. This interatomic potential has been used before by several groups to model dislocations 39,40 and plastic deformation of STO. 41 It was found to be more suitable for studying extended defects than more elaborate shell-model potentials 42 and predicts mechanical properties of STO and defect properties sufficiently well for the type of large-scale simulation conducted here.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…In parallel, recent theoretical calculations related to the physics of dislocations in MgSiO 3 bridgmanite confirm that the lattice friction remains very high, even at high temperature 42 , which account very well for the high stress levels observed in experiments 36 . Indeed, insights into slip systems and plastic anisotropy of MgSiO 3 bridgmanite were first gained from modelling dislocation cores and lattice friction at the atomic scale 4347 . More recently, high temperature dislocation glide has been characterized from the modelling of thermally activated processes underlying dislocation glide at finite temperature 42 .…”
Section: Introductionmentioning
confidence: 99%